Field notes contributed by Raymond L. Cummins, winter 1981-1982 - Cummins, Raymond L.et al (1981)
Field notes were contributed by Raymond L. Cummins. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1981-1982. Epson - sheet feed